Advances of cancer-associated fibroblasts in liver cancer - Hao Peng; Erwei Zhu; Yewei Zhang (Biomarker Research, 2022)
Abstract Liver cancer is one of the most common malignant tumors worldwide, it is ranked sixth in incidence and fourth in mortality. According to the distinct origin of malignant tumor cells, liver cancer is mainly divided into hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA). Since most cases are diagnosed at an advanced stage, the prognosis of liver cancer is poor. Tumor growth depends on the dynamic interaction of various cellular components in the tumor microenvironment (TME). As the most abundant components of tumor stroma, cancer-associated fibroblasts (CAFs) have been involved in the progression of liver cancer. The interplay between CAFs and tumor cells, immune cells, or vascular endothelial cells in the TME through direct cell-to-cell contact or indirect paracrine interaction, affects the initiation and development of tumors. Additionally, CAFs are not a homogeneous cell population in liver cancer. Recently, single-cell sequencing technology has been used to help better understand the diversity of CAFs in liver cancer. In this review, we mainly update the knowledge of CAFs both in HCC and CCA, including their cell origins, chemoresistance, tumor stemness induction, tumor immune microenvironment formation, and the role of tumor cells on CAFs. Understanding the context-dependent role of different CAFs subsets provides new strategies for precise liver cancer treatment.